Chemical and thermal performance analysis of a solar thermochemical reactor for hydrogen production via two-step WS cycle - Sharma J.P.; Kumar R.; Ahmadi M.H.; Mukhtar A.; Yasir A.S.H.M.; Sharifpur M.; Ongar B.; Yegzekova A. (Elsevier Ltd, 2024)
Ceria-based H2O/CO2-splitting solar-driven thermochemical cycle produces hydrogen or syngas. Thermal optimization of solar thermochemical reactor (STCR) improves the solar-to-fuel conversion efficiency. This research presents two conceptual designs and thermal modelling of RPC-ceria-based STCR cavities to attain the optimal operating conditions for CeO2 reduction step. Presented hybrid geometries consisting of cylindricalhemispherical and conical frustumhemispherical structures. The focal point was positioned at x = 0, -10 mm, and -20 mm from the aperture to examine the flux distribution in both solar reactor configurations. Case-1 with 2 milliradian S.E (slope error) yields a 27% greater solar flux than case-1 with 4 milliradians S.E, despite the 4 milliradian S.E produces an elevated temperature in the reactor cavity. The mean temperature in the reactive porous region was most significant for case-2 (x = -10 mm) with 4 mrad S.E for model-2, reaching 1966 K and 2008 K radially and axially, respectively. In case-2 (x = -10 mm) for 4 mrad S.E, model-1 attained 1720 K. The efficiency analysis shows that the highest conversion efficiency value was obtained to be 7.95% for case-1 with 4 milliradian S.E. 2023 The Author(s)